Does glucose affect the de‐esterification of methyl ferulate by Lactobacillus buchneri?. Issue 2 (29th November 2019) - Mogodiniyai Kasmaei, Kamyar; Schlosser, Dietmar; Sträuber, Heike; Kleinsteuber, Sabine
Abstract: Silage, the fermented product from anaerobic storage of forage crops with high water contents (50%–70%), is normally used as animal feed but also for the production of biofuels and value‐added products. To improve the utilization of plant fibers during ensiling, previous attempts have aimed at breaking linkages between lignin and hemicellulose by use of Lactobacillus buchneri LN 4017 (ATCC PTA‐6138), a feruloyl esterase (FAE)‐producing strain, but results have been inconsistent. Normally, there are sufficient amounts of readily available substrates for bacterial growth in silage. We thus hypothesized that the inconsistent effect of L. buchneri LN 4017 on the digestibility of silage fibers is due to the catabolic repression of FAE activity by substrates present in silage (e.g., glucose). To test this hypothesis, we analyzed the effect of glucose on the de‐esterification of methyl ferulate (MF), a model substrate used for FAE activity assays. At three glucose:MF ratios (0:1, 1:1, and 13:1), the bacteria continued hydrolyzing MF with increasing glucose:MF ratios, indicating that the de‐esterification reaction was not repressed by glucose. We therefore conclude that the de‐esterification activity of L. buchneri LN 4017 is not repressed by silage substrates during ensiling. Abstract : In this work, we studied de‐esterification activity of Lactobacillus buchneri in presence of glucose. Our results indicated that glucose did not repress the de‐esterification reaction. The results obtained provide information about catabolic capacity of L. buchneri .